2018
DOI: 10.1128/jb.00580-17
|View full text |Cite
|
Sign up to set email alerts
|

History of CRISPR-Cas from Encounter with a Mysterious Repeated Sequence to Genome Editing Technology

Abstract: Clustered regularly interspaced short palindromic repeat (CRISPR)-Cas systems are well-known acquired immunity systems that are widespread in archaea and bacteria. The RNA-guided nucleases from CRISPR-Cas systems are currently regarded as the most reliable tools for genome editing and engineering. The first hint of their existence came in 1987, when an unusual repetitive DNA sequence, which subsequently was defined as a CRISPR, was discovered in the genome during an analysis of genes involved in phosphate meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
235
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(245 citation statements)
references
References 99 publications
3
235
1
6
Order By: Relevance
“…This suggests that profound and unexpected biological insights may one day come out from the analysis of k-mer frequencies, and in particular from their most improbable fluctuations. In a daring parallel with the delayed understanding of the CRISPR/CAS system from the initial spotting of intriguing repeats 33 , we would like to expect that the pandoraviridae “AGCT” distribution anomaly might lead to the discovery of a novel defense mechanism against viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that profound and unexpected biological insights may one day come out from the analysis of k-mer frequencies, and in particular from their most improbable fluctuations. In a daring parallel with the delayed understanding of the CRISPR/CAS system from the initial spotting of intriguing repeats 33 , we would like to expect that the pandoraviridae “AGCT” distribution anomaly might lead to the discovery of a novel defense mechanism against viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The first CRISPRs were detected by Ishino et al 1987 in iap gene of Escherichia coli genome. Ishino et al discovered an orderly spaced short repeats located in the iap gene but their function had not been exactly figured out (Ishino et al, 1987;Ishino et al, 2018). In the following years, similar repeat sequences were determined in Mycobacterium tuberculosis, Haloferax mediterranei, Methanocaldococcus jannaschii, Thermotoga maritima and other bacteria -archaea (Sorek et al, 2008).…”
Section: The Crispr-cas Gene Editing Systemmentioning
confidence: 99%
“…These researchers concluded that BNA NC -containing probes coupled to fluorescently labeled microspheres are suitable reagents to detect DNMT3A R888 mutations [134]. palindromic repeats" (CRISPR) is specific and, in a surprisingly analogous mode to vertebrate immune systems, it requires previous exposure to the foreign genetic material to create a memory record that can elicit a quick response in future exposure events [138].…”
Section: Diagnostics Of Hematologic Malignancies By the Detection Of mentioning
confidence: 99%
“…In particular, the class 2, type II system, which depends on the endonuclease Cas9, has been developed as a tool for numerous applications such as the generation of mutants, gene editing, bacterial species identification and typing, antibacterial agents, genome wide screening in mammalian cells, regulation of gene expression (through the use of dCas9, a derivative that lost the cleavage activity), and others [138][139][140][141][142].…”
Section: Diagnostics Of Hematologic Malignancies By the Detection Of mentioning
confidence: 99%